Principles of optimising Energy Fixation in Forest Crops - Gurumurti, K. (Indian Forester, 1981)
Plants are the largest global solar energy converters despite their efficiency being a mere 0.1 to 0.2 percent. Based on theoretical considerations plants can attain an efficiency of 6.6 percent. However, even under intensive agriculture using highly productive crops like sugar cane 3% efficiency is rarely exceeded. In case of forest plants it is rarely above O.5 percent. There is considerable scope to improve the efficiency to 1% which amounts to doubling of produtivity of forests. Methods to improve the energy fixation efficiency of forest crops using multistoreyed plantations, planting fast growing species with close spacing and short rotations. and carbondioxide enrichment and discussed. A workout for power generation, using wood fuel perpetually, for villages on decentralised basis is also presented.